2017
DOI: 10.1556/0806.45.2017.010
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of defense genes expression in maize upon infection with Peronosclerospora sorghi

Abstract: Downy mildew, caused by Peronosclerospora sorghi is one of the important diseases affecting maize (Zea mays L.) production worldwide. Several downy mildew resistant maize lines have been identified. However, variability in the degree of resistance among maize genotypes to P. sorghi has been reported. In the present study the molecular basis of resistance of maize to P. sorghi was studied by using differential-display reverse transcription PCR (DDRT-PCR) technique. Maize seedlings of downy mildew resistant (MAI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…This protein is up accumulated by 1.5-fold at 6 hpi but its' accumulation is significantly affected at 12 hpi (-2.1-fold). Serine/threonine kinase genes have been described to have a constitutive and high-level expression in resistant non-inoculated plants, in contrast to susceptible plants were no expression is detected [34]. It has also been suggested that this protein may be involved in boosting resistance against plant pathogens, since they are involved in signalling the presence of the pathogen in the plant [35,36].…”
Section: Translation and Protein Transport Processes Are Initially Bomentioning
confidence: 99%
“…This protein is up accumulated by 1.5-fold at 6 hpi but its' accumulation is significantly affected at 12 hpi (-2.1-fold). Serine/threonine kinase genes have been described to have a constitutive and high-level expression in resistant non-inoculated plants, in contrast to susceptible plants were no expression is detected [34]. It has also been suggested that this protein may be involved in boosting resistance against plant pathogens, since they are involved in signalling the presence of the pathogen in the plant [35,36].…”
Section: Translation and Protein Transport Processes Are Initially Bomentioning
confidence: 99%